Prediction of the Temperature Stability of Dams Built of Local Materials on Permafrost Bases - Tsytovich,N. A.; Ukhova,N. V.; Ukhov,S. B. (1974)
Contents: Concerning the construction of dams from local material on permafrost footings; Features in heat exchange in rocks as a material for dams and foundations; Prediction of heat exchange in nonfiltering dams; Practical methods for calculating the temperature fields of frozen dams and their footings; Experimental studies of temperature in regime in models of frozen dams. Draft trans. of mono. Prognoz Temperaturnoi Ustoichivosti Plotin iz Mestnykh Materialov na Vechnomerzlykh Osnovaniyakh, Leningrad, 1972 p4-142.